2007
DOI: 10.1177/1087054707305155
|View full text |Cite
|
Sign up to set email alerts
|

Attention Problems and Hyperactivity as Predictors of College Grade Point Average

Abstract: The implications of these results for assessing symptoms of inattention and hyperactivity in college students are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 14 publications
5
36
0
2
Order By: Relevance
“…Indeed, recent findings with college students with ADHD support the continuation of inattentive symptoms and the decrease of hyperactivity symptoms based on parental and self-reports [Frazier et al, 2007]. Studies also suggest that attention problems are the most robust predictor of college student grade point average (GPA) relative to hyperactivity/impulsivity symptoms [Schwanz et al, 2007].…”
Section: Adhd In College Students: Developmental Findingsmentioning
confidence: 94%
“…Indeed, recent findings with college students with ADHD support the continuation of inattentive symptoms and the decrease of hyperactivity symptoms based on parental and self-reports [Frazier et al, 2007]. Studies also suggest that attention problems are the most robust predictor of college student grade point average (GPA) relative to hyperactivity/impulsivity symptoms [Schwanz et al, 2007].…”
Section: Adhd In College Students: Developmental Findingsmentioning
confidence: 94%
“…Compared to college students without ADHD, students with ADHD have many more academic problems, including higher rates of dropout (Blase et al., ; Heiligenstein et al., ; Weyandt & DuPaul, ). Inattentive symptoms are particularly linked to poorer academic functioning (Frazier et al., ; Rabiner et al., ), including grade point average (GPA; Schwanz et al., ).…”
Section: Factor Structure Of Adhd and Sctmentioning
confidence: 99%
“…As noted above, one hypothesis was that the stimulant doses required to control the hyperactivity of ADHD-diagnosed children might be greater than doses that are most effective for improving cognition. However, unlike children, college students are less likely to be characterized as hyperactive, and more commonly diagnosed with, or to self-report, the symptom of inattention (Frazier et al, 2007;Norwalk et al, 2009;Rabiner et al, 2008;Schwanz et al, 2007) even without a specific diagnosis of ADHD (Lewandowski et al, 2008). Therefore, undergraduates should be able to determine the amount of stimulant medication that would presumably improve their attention and concentration without having to control hyperactivity as well.…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%
“…Some (Advokat et al, 2008;Blase et al, 2009) have found significantly lower GPAs in ADHDdiagnosed college students relative to non-ADHD controls. Not surprisingly, higher levels of ADHD symptomatology are consistently associated with poor study habits, skills and academic adjustment, and greater self-reports of attention deficits (Norwalk et al, 2009;Schwanz et al, 2007). Recent surveys (Rabiner et al, 2008;2009a;2009b) show no difference between the ADHD-diagnosed undergraduates who used stimulant medications and those who didn't, in regard to self-reported concerns with their academic performance, problems of inattentiveness, hyperactivity, depression or their social life.…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%